Importance of activity and physical condition in school performance: a literature review: Importancia de la actividad y la condición física en el desempeño escolar: una revisión de literatura (Papeles, 2021)
The aim of this article was to carry out a bibliographic synthesis of the scientific studies published in the last six years that assess the relationship between physical activity, physical condition and academic performance in schoolchildren and adolescents. The bibliographic search was based on articles published between 2014 and 2019, in the following databases: Scopus, Google Scholar, Scielo and Redalyc. The used keywords were physical activity, physical education, physical condition, school sport, cognitive performance, executive functions, and academic performance in adolescents. There were analyzed 96 articles from which 64 were selected for the review. The selected categories were physical activity and its benefits, suggested levels of physical activity, physical condition and academic or cognitive performance, physical activity and sport as enhancers in the development of executive functions, and the academic performance and physical activity. The results indicate that the levels of activity and physical condition may be positively associated with the improvement in academic performance by developing some executive functions, such as working memory, cognitive flexibility, capacity for inhibition and sequential planning. The findings contribute to consolidate the importance of regular physical activity on the cognitive development of adolescents and shows a way of working that can be adequate to achieve an increase in the academic performance of students. However, it is necessary to continue investigating other studies that analyze these effects in more detail.
Keywords: physical activity; physical condition; excecutive function; academic performance